2002
DOI: 10.1124/jpet.102.034140
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Organic Cation Transporter 1 in Hepatic and Intestinal Distribution of Metformin

Abstract: Metformin, a biguanide, is widely used as an oral hypoglycemic agent for the treatment of type 2 diabetes mellitus. The purpose of the present study was to investigate the role of organic cation transporter 1 (Oct1) in the disposition of metformin. Transfection of rat Oct1 cDNA results in the time-dependent and saturable uptake of metformin by the Chinese hamster ovary cell line with K m and V max values of 377 M and 1386 pmol/min/mg of protein, respectively. Buformin and phenformin, two other biguanides, were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
320
1
3

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 401 publications
(333 citation statements)
references
References 32 publications
9
320
1
3
Order By: Relevance
“…[22][23][24][25] Our transport studies identify metformin as an OCT3 substrate (Fig. 4) with an affinity for OCT3 similar to that for OCT1 21,28,29 and a twofold higher maximal transport rate compared with OCT1. Recently, Shu et al 29,33 showed significant alteration of pharmacokinetics of metformin and its glucose-lowering effect in individuals with reduced-function OCT1 variants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[22][23][24][25] Our transport studies identify metformin as an OCT3 substrate (Fig. 4) with an affinity for OCT3 similar to that for OCT1 21,28,29 and a twofold higher maximal transport rate compared with OCT1. Recently, Shu et al 29,33 showed significant alteration of pharmacokinetics of metformin and its glucose-lowering effect in individuals with reduced-function OCT1 variants.…”
Section: Discussionmentioning
confidence: 99%
“…27 The impact of an altered OCT1-mediated drug transport on pharmacokinetics can be exemplified by metformin. In Oct1 ϩ/ϩ mice, the liver concentration of metformin was approximately 30 times higher than in Oct1 Ϫ/Ϫ mice; 28 moreover, the blood glucose-lowering effect of metformin was completely abolished in Oct1 Ϫ/Ϫ mice. 29 In humans, several OCT1 variants with reduced transport function, including metformin transport, have been identified.…”
mentioning
confidence: 89%
“…Hepatic uptake of small organic cations includes essential substrates for biosynthetic pathways as well as xenobiotics and is of major importance because the liver represents the main site for biotransformation in the body. For example, hepatic uptake of metformin in Oct1 knockout mice is reduced more than 30 times below levels of uptake in wild-type mice, 35 and results in lower blood concentrations of lactate. 36 Transport of metformin into the liver is essential for its antidiabetic effect that is mediated by inhibition of complex 1 of the mitochondrial respiratory chain in the hepatocyte.…”
Section: Discussionmentioning
confidence: 99%
“…OCT1 and OCT3 are expressed on the sinusoidal membrane of hepatocytes and play a major role in the uptake of metformin from blood into the hepatocytes 59 . In 2002, elegant studies from the Sugiyama group showed that OCT1 is responsible for the hepatic uptake and intestinal distribution of metformin 60,61 Further, reduced hepatic metformin concentrations have been shown to affect metformin response in mice 62 . In particular, the hepatic accumulation of metformin was significantly greater in wildtype mice than in Oct1 knockout mice after a single oral dose of the drug.…”
Section: Transporters Involved In Metformin Pharmacologic Actionmentioning
confidence: 99%